The Dimensionality Transition between Three-Dimensional and Two-Dimensional Organic Microcrystals: Specific Symmetry and Selective Adhesion - Wang, Sha-Sha (ACS Omega, 2020)
[Image: see text] A three-dimensional–two-dimensional dimensionality transition of organic microcrystals was performed via elongated octahedrons, oblique octahedrons, diamond-like particles, and parallelograms using nonplanar 2,7-di(9H-carbazol-9-yl)spiro[fluorene-9,9′-xanthene] molecules. The specific crystal symmetry and selective adhesion of P123 on the {11–1}s facet are supposed to induce the morphological transition.